Tinjauan literatur: Stres Remaja (Jurnal Ilmiah Psikologi MIND SET, 2025)
Persistent adolescent stress, if not properly addressed, can have negative impacts on the physical and psychological health of adolescents. This study aims to identify attachment patterns contributing to adolescent stress levels through a literature review method, focusing on the roles of parental attachment, peer attachment, school attachment, and attachment to God as primary predictors. Attachment influences stress levels in adolescents. The study integrates literature published over the past decade to identify dominant attachment patterns and their impacts on adolescent stress. Literature review findings indicate that strong attachment to parents, peers, and school serves as significant protective factors in reducing stress levels, while attachment to God provides spiritual support that aids in stress management.